A comparative study of achene morphology in Korean Polygonaceae (Bangladesh Journal of Plant Taxonomy, 2018)
A comparative macro- and micromorphological study was conducted on achenes of Korean Polygonaceae comprising 45 taxa under 10 genera using a Stereo-microscope (SM) and Scanning Electron Microscope (SEM) to evaluate the taxonomical relevance of achene morphological characteristics. The achene shape is lenticular, biconvex, trigonous, or spheroidal. The largest achenes are found in Fagopyrum esculentum Moench (5.80–6.70 × 3.90–4.40 mm) and Rheum rhabarbarum L. (5.00–6.50 × 4.00–5.20 mm), and the smallest is found in Rumex maritimus L. (1.17–1.41 × 0.60–0.84 mm). Three types of embryo shape (curved, straight, and folded) and two types of embryo position (plane and parietal) can be distinguished. Most taxa have a curved embryo shape with plane position. Four types of surface patterns (smooth, papillae, tuberculate, or small pits) are observed. The surface sculpture or embryo type is rather consistent at the generic or tribal level, and the comprehensive consideration of achene characteristics is also useful at the species level. The achene morphology is described in detail, compared, and illustrated. The taxonomic significance of the achene morphology is discussed.